2009
DOI: 10.1086/644751
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bloodstream Infections by Use of Daily Chlorhexidine Baths for Patients at a Long-Term Acute Care Hospital

Abstract: Daily chlorhexidine baths appeared to be an effective intervention to reduce rates of CVC-associated BSI in an LTACH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 19 publications
3
75
3
3
Order By: Relevance
“…The chlorhexidine gluconate arm. [8][9][10][11] In the fifth study, 12 which was of patients in surgical intensive care units, significant differences were not found.…”
Section: Recommendationsmentioning
confidence: 89%
See 2 more Smart Citations
“…The chlorhexidine gluconate arm. [8][9][10][11] In the fifth study, 12 which was of patients in surgical intensive care units, significant differences were not found.…”
Section: Recommendationsmentioning
confidence: 89%
“…Four quasiexperimental studies 8,[10][11][12] and 1 cross-over study 9 in a pre-post study design were retrieved (Table 1). Most studies were set in an intensive care unit, but one study 8 was conducted in a long-term acute care hospital.…”
Section: Clabsimentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance bundle used at NBIMC was based on a previous construct from the CDC 2002 guidelines which includes: assessing the continued need for the catheter every day, performing catheter site care with chlorhexidine at dressing changes and changing gauze dressings every 2 days and clear dressings every 7 days (and more frequently if soiled, damp, or loose). Using a 2% chlorhexidine for daily skin cleansing was established by Munoz-Price et al after they evaluated the effect of chlorhexidine bathing of patients on the rate of CLABSI in a 70-bed long-term acute care hospital [14]. Their work demonstrated that this intervention reduces the rate of CLASBI from 9.5 to 3.8 per 1,000 catheter days.…”
Section: Methodsmentioning
confidence: 99%
“…Bleasdale and colleagues demonstrated, in medical ICU patients, decreased primary BSI infection rates in the CHG intervention group compared to standard treatment, respectively, 4.1 vs. 10.4 infections per 1,000 patient days (5). Munoz-Price et al reported a 99% reduction in the CLA-BSI rate in long-term acute care hospital patients bathed daily with CHG (6). O'Horo's 2012 metaanalysis of one randomized and 11 non-randomized trials showed daily bathing with CHG reduced the incidence of BSIs in medical ICU patients (7); the optimal frequency and method of application were to be determined.…”
mentioning
confidence: 99%